Pengaruh Literasi Ekonomi Dan Tingkat Penggunaan Media Sosialterhadap Minat Berwirausaha Pada Mahasiswa FEB Universitas Muhammadiyah Metro - Febriyanto, Febriyanto; Fitriani, Fitriani; Setiawan, Dandi Rama (Universitas Muhammadiyah Metro, 2023)
This researchwas conducted in order to determine the effect of economic literacy and thelevel of use of social media on the entrepreneurial interest of FEB students, MuhammadiyahMetro University. The type of research used is quantitative research. Sampling techniqueusing Accidental Sampling. Only 90 samples used were in accordance with predeterminedcriteria. The data used is primary data with the distribution of questionnaires in the form of alist of questions with several alternative answers for respondents. The statistical test used totest the hypothesis is multiple linear regression analysis and tested using the statisticalpackages for the social science (SPSS) version 25 program. Based on the results of statisticaltests, it shows that economic literacy and the level of use of social media have a positive orsignificant influence on the entrepreneurial interest of FEB students, Muhammadiyah MetroUniversity.